The language of the New Testament : context, history, and development - Porter, Stanley E., 1956-; Pitts, Andrew W. (Brill, 2013)
In The Language of the New Testament, Stanley E. Porter and Andrew W. Pitts assemble an international team of scholars whose work has focused on the Greek language of the earliest Christians in terms of its context, history and development.
Stanley E. Porter and Andrew W. Pitts. The Disclosure Formula in the Epistolary Papyri and in the New Testament: Development, Form, Function, and SyntaxBeth M. Stovell. Seeing the Kingdom of God, Seeing Eternal Life: Cohesion and Prominence in John 3:1-15 and the Apocryphal Gospels in Terms of Metaphor Use; Index of Modern Authors; Index of Ancient Sources.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 072
Keywords: Bible -- Language, style; Bible -- Criticism, interpretation, etc; Bible; Greek language, Biblical; Greek language, Biblical; RELIGION / Biblical Studies / New Testament; Electronic books; Criticism, interpretation, etc